Improving process aspect of oral examination as assessment tool in undergraduate biochemistry by introducing structured oral examination: an observational study in India based on a survey among stakeholders - Rinchu Loomba; Nandita Maini Jindal (Korean Journal of Medical Education, 2024)
Purpose The traditional method of oral examination, though a good tool for assessing the depth and breadth of student’s knowledge, has its shortcomings. A variable number of questions with variable difficulty levels by different examiners with different expectations can introduce bias in scores. The process aspect of oral examinations of first-year undergraduate medical students was improved by structuring them and by creating uniformity in the number, time, and difficulty level of questions for assessment, and feedback was taken regarding its acceptance as an improved tool of assessment. Methods After finalizing the topics, questions from a viva viewpoint were structured and categorized into three difficulty levels covering all aspects of chosen topics validated by subject experts. The number of questions asked per difficulty level, time, and marks given to each question was pre-decided. After briefing the students, the structured viva was conducted, and feedback was taken from students and examiners. Results The majority (87%) of first-year undergraduate students undertook the structured viva and filled in the feedback form. Nearly all students felt that the structured oral examination was a fair and unbiased assessment tool with less subjectivity compared to traditional viva. Most students (83.9%) felt that the topics were comprehensively covered, and 96.4% of students felt less stressed. Among examiners, there was 100% agreement on the uniformity of questions asked, topics covered, less subjectivity, and no carryover effect. Conclusion The examiners have accepted it as one of the formative assessment tools for future batches of students and are ready to explore its utility as a summative assessment tool.